ANALISIS KESESUAIAN PELAKSANAAN PEMBERSIHAN KAMAR DENGAN STANDAR HOUSEKEEPING DI HOTEL M-ONE SENTUL - Muhammad Alfian Wijayanto; Cindy Henriette Posumah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Service quality in the hotel industry is strongly influenced by the performance of the Housekeeping Department in maintaining guest room cleanliness, comfort, and readiness. This study was motivated by the discovery of inconsistencies in room cleaning standards at M-One Hotel Sentul, particularly under high operational pressure such as full occupancy, late check-out, and early check-in. The purpose of this study was to analyze the compliance of room cleaning implementation with applicable Housekeeping standards and to identify the factors causing non-compliance. This research used a qualitative approach with direct observation, documentation, and in-depth interviews involving five informants consisting of four room attendants and one Housekeeping Supervisor. Informants were selected using purposive sampling. Data were analyzed interactively through data reduction, data presentation, conclusion drawing, and triangulation. The findings show that the preparation, bed making, and bathroom cleaning stages were implemented in accordance with the established procedures. However, inconsistencies were still found in dusting, amenities replenishment, and final checking. The main contributing factors were limited working time, high occupancy, late check-out, early check-in, linen availability, incomplete amenities, and suboptimal coordination between Housekeeping and Front Office. The study recommends strengthening supervision, logistics management, interdepartmental coordination, and double checking to maintain consistent service quality.